Identidades nacionales en América Latina Discursos, saberes, representaciones - Russ, Carla (Historamericana, 2022)
This volume elucidates the phenomenon of the nation from a historical-critical perspective and investigates the origins, the causes of success, the ways of diffusion and the problematic implications of the discourses of national identity in Latin America.